Mapping the salinity status of agricultural soils between Kırıkhan-Kumlu in the Eastern Mediterranean region of Turkey with Geographic Information Systems (GIS) - Gürler, Kübra; Yalçın, Mehmet (Journal of Environmental Engineering and Landscape Management, 2024)
In this study, it was aimed to determine the salinity status of agricultural soils between Kırıkhan-Kumlu in the Eastern Mediterranean region of Turkey by mapping with Geographic Information Systems (GIS). For this purpose, a total of 60 soil samples were taken from 0–20 and 20–40 cm depths and from 30 different points to represent the agricultural soils of Kırıkhan-Kumlu region in the Eastern Mediterranean region of Turkey. In the soil samples, pH, cation exchange capacity (CEC) and exchangeable cation (ECC) values were determined to determine some soil properties. Total salt, salinity class, sodium adsorption rate (SAR), exchangeable sodium percentage (ESP) and soluble cations (Na, Ca and Mg) were determined to determine the salinity status of the soils.According to the results of the research; as a result of the analysis carried out to determine the salinity status of the soils; pH values were determined between 6.91–7.98; total salt content between 0.02–0.13%; SAR values between 0.023–0.044 me/100 gr; ESP values between 0.35–2.96%; soluble Na content between 0.019–0.034 me/100 gr; soluble Ca content between 0.018–0.245 me/100 gr and soluble Mg content between 0.037–0.113 me/100 gr. In addition, by applying the ESP-SAR regression relationship of the soils, it was revealed that the soils tended to alkalize towards the lower layers. The salinity values obtained as a result of the study were transferred to the Geographic Information Systems (GIS) environment and interpolated by Kriging method and a salinity map of the study area was created. In conclusion, as a result of the research conducted in the soils of the study area in the Eastern Mediterranean region, it was determined that all of the agricultural soils of Kırıkhan-Kumlu region were classified as non-saline and that the soils did not have any problems in terms of salinity.